Attitudes towards research and academic performance in students of a private university in Lima - Rosario Quiroz, Fernando Joel (2016)
This article investigates attitudes toward research and its relation to academic performance in a group of first cycle students from a private university. Method was worked with students of psychology and engineering. A sample of 420 people selected through an intentional sampling was used. We used a scale of attitudes towards the research developed for the present research, to measure the academic performance we worked with the average grades obtained in the courses where they elaborate formative research works. The most significant findings indicate that there is no relationship between attitudes towards research and academic achievement. There is only a relationship between the cognitive and affective components of attitude toward research and academic performance.